PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VISUAL BLOCK PROGRAMMING (VBP) PADA MATA PELAJARAN DASAR-DASAR TEKNIK JARINGAN KOMPUTER DAN TELEKOMUNIKASI DI SMKN 1 BONJOL - Nurfazila, Nurfazila; Mulyono, Heri; Darman, Regina Ade (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
This research aims to develop Visual Block Programming (VBP)-based learning media for the Basics of Computer Network and Telecommunications Engineering subjects at SMKN 1 Bonjol, with a focus on Basic Orientation material for Computer Network and Telecommunications Engineering. The research method used is research and development, by applying the ADDIE development model. The research subjects consisted of 35 class This research uses a validity instrument in the form of a questionnaire filled out by 6 validators to measure the validity of the media being developed. This research used 3 media validators and 3 material validators to measure the validity of Visual Block Programming (VBP) based learning media products. The media validity result was 0.78519 in the "Valid" category, while the material validity reached 0.95238 in the "Valid" category. Therefore, it can be concluded that this VBP learning media is valid in terms of content and design. Apart from that, the teacher's practicality results show that this learning media received a score of 93.30% in the "Very Practical" category. Likewise, students' practicality achieved a score of 85.54% in the "Very Practical" category. This indicates that the VBP learning media is very effective and practical to use in the learning process for the Basics of Computer Network and Telecommunications Engineering at SMKN 1 Bonjol in the 2023/2024 academic year.